Follicular Lymphoma: Recent and Emerging Therapies, Treatment Strategies, and Remaining Unmet Needs. (25th July 2019) - Matasar, Matthew J.; Luminari, Stefano; Barr, Paul M.; Barta, Stefan K.; Danilov, Alexey V.; Hill, Brian T.; Phillips, Tycel J.; Jerkeman, Mats; Magagnoli, Massimo; Nastoupil, Loretta J.; Persky, Daniel O.; Okosun, Jessica
Abstract: : Follicular lymphoma (FL) is a heterogeneous disease with varying prognosis owing to differences in clinical, laboratory, and disease parameters. Although generally considered incurable, prognosis for early‐ and advanced‐stage disease has improved because of therapeutic advances, several of which have resulted from elucidation of the biologic and molecular basis of the disease. The choice of treatment for FL is highly dependent on patient and disease characteristics. Several tools are available for risk stratification, although limitations in their routine clinical use exist. For limited disease, treatment options include radiotherapy, rituximab monotherapy or combination regimens, and surveillance. Treatment of advanced disease is often determined by tumor burden, with surveillance or rituximab considered for low tumor burden and chemoimmunotherapy for high tumor burden disease. Treatment for relapsed or refractory disease is influenced by initial first‐line therapy and the duration and quality of the response. Presently, there is no consensus for treatment of patients with early or multiply relapsed disease; however, numerous agents, combination regimens, and transplant options have demonstrated efficacy. Although the number of therapies available to treat FL has increased together with an improved understanding of the underlying biologic basis of disease, the best approach to select the most appropriate treatment strategy for an individual patient at a particular time continues to be elucidated. This review considers prognostication and the evolving treatment landscape of FL, including recent and emergent therapies as well as remaining unmet needs. Implications for Practice: In follicular lymphoma, a personalized approach to management based on disease biology, patient characteristics, and other factors continues to emerge. However, application of current management requires an understanding of the available therapeutic options for first‐line treatment and knowledge of current development in therapies for previously untreated and for relapsed or refractory disease. Thus, this work reviews for clinicians the contemporary data in follicular lymphoma, from advances in characterizing disease biology to current treatments and emerging novel therapies. Abstract : Therapeutic advances have improved prognosis for follicular lymphoma, although the disease is still incurable. This comprehensive clinical review considers prognostic approaches and the treatment landscape for follicular lymphoma, including emerging therapies and unmet needs.